The role of DNA methylation as biomarkers in the clinical management of lung cancer. (August 2013) - Fleischhacker, Michael; Dietrich, Dimo; Liebenberg, Volker; Field, John K; Schmidt, Bernd
It is now widely accepted that cancer is caused by complex interactions between genetic and epigenetic factors and the environment. Only in the last 20 years, DNA methylation has been recognized as an epigenetic mechanism, which plays a major role during the development and progression of cancers. Accordingly, DNA methylation profiling provides a useful source for biomarkers in distinct clinical questions; for example, risk stratification, diagnosis, staging, prognosis and therapy-response prediction. In the last 10 years, not only has an increase in the number of papers published on this subject been seen, but also an impressive technological advancement allowing for the highly sensitive and accurate quantification of DNA methylation biomarkers in challenging sample types. However, the development of a suitable biomarker with appropriate assay technology is not trivial. This is especially true for the choice of biomarkers used for the management of early diagnosis of lung cancer.